Born out of place migrant mothers and the politics of international labor - Constable, Nicole (Hong Kong University Press, 2014)
"Hong Kong is a meeting ground for migrant domestic workers, traders, refugees, asylum seekers, tourists and businessmen, and local residents. At the heart of this book are the stories and experiences of migrant mothers from Indonesia and the Philippines, their South Asian, African, Chinese, and Western expatriate partners, and their Hong Kong born babies. Constable gives voice to the immigrant mothers in this Asian world city and, in the process, raises a serious question: do we regard immigrants as people, or just workers? This accessible ethnography provides insight into global problems of mobility, family, and citizenship and points to the consequences, creative responses, melodramas, and tragedies of labor and migration policies"--Provided by publisher.